Plant growth promoting potential of urea doped calcium phosphate nanoparticles in finger millet (Eleusine coracana (L.) Gaertn.) under drought stress - Mishra, Dhruv; Chitara, Manoj Kumar; Upadhayay, Viabhav Kumar; Singh, Jagat Pal; Chaturvedi, Preeti (Frontiers in Plant Science, 2023)
Drought is a leading threat that impinges on plant growth and productivity. Nanotechnology is considered an adequate tool for resolving various environmental issues by offering avant-garde and pragmatic solutions. Using nutrients in the nano-scale including CaP-U NPs is a novel fertilization strategy for crops. The present study was conducted to develop and utilize environment-friendly urea nanoparticles (NPs) based nano-fertilizers as a crop nutrient. The high solubility of urea molecules was controlled by integrating them with a matrix of calcium phosphate nanoparticles (CaP NPs). CaP NPs contain high phosphorous and outstanding biocompatibility. Scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and X-ray diffraction analysis (XRD) were used to characterize the fabricated NPs. FE-SEM determined no areas of phase separation in urea and calcium phosphate, indicating the successful formation of an encapsulated nanocomposite between the two nano matrices. TEM examination confirmed a fibre-like structure of CaP-U NPs with 15 to 50 nm diameter and 100 to 200 nm length. The synthesized CaP-U NPs and bulk urea (0.0, 0.1 % and 0.5 %) were applied by foliar sprays at an interval of 15 days on pre-sowed VL-379 variety of finger millet (Eleusine coracana (L.) Gaertn.), under irrigated and drought conditions. The application of the CaP-U NPs significantly enhanced different plant growth attributes such as shoot length (29.4 & 41%), root length (46.4 & 51%), shoot fresh (33.6 & 55.8%) and dry weight (63 & 59.1%), and root fresh (57 & 61%) and dry weight (78 & 80.7%), improved pigment system (chlorophyll) and activated plant defense enzymes such as proline (35.4%), superoxide dismutase (47.7%), guaiacol peroxidase (30.2%), ascorbate peroxidase (70%) under both irrigated and drought conditions. Superimposition of five treatment combinations on drought suggested that CaP-U NPs at 0.5 followed by 0.1 % provided the highest growth indices and defense-related enzymes, which were significantly different. Overall, our findings suggested that synthesized CaP-U NPs treatment of finger millet seeds improved plant growth and enzymatic regulation, particularly more in drought conditions providing insight into the strategy for not only finger millet but probably for other commercial cereals crops which suffer from fluctuating environmental conditions.